2016
DOI: 10.1097/htr.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions Deficits After Severe Traumatic Brain Injury

Abstract: Behavioral changes were more frequent and severe than cognitive deficits, at least as assessed with traditional testing. The present results also suggest that a shortened battery may provide a rapid screening method with reasonable sensitivity to detect deficits of executive functions in patients with severe traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 65 publications
1
14
0
1
Order By: Relevance
“…In our study, disinterest and indifference, social behavior disorders, and irritability-aggressiveness were also very frequent behavioral changes reported by professionals and closest relatives as compared to pre-injury. Estimated rates for disinterest and indifference [49% in this study and 46.3% in the study by Azouvi et al (21)] or irritability-aggressiveness (47 vs. 42.6%) were close to those found by Azouvi et al (21). For social behavior disorders, the estimated rate was higher in our study (49 vs. 24.1%).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In our study, disinterest and indifference, social behavior disorders, and irritability-aggressiveness were also very frequent behavioral changes reported by professionals and closest relatives as compared to pre-injury. Estimated rates for disinterest and indifference [49% in this study and 46.3% in the study by Azouvi et al (21)] or irritability-aggressiveness (47 vs. 42.6%) were close to those found by Azouvi et al (21). For social behavior disorders, the estimated rate was higher in our study (49 vs. 24.1%).…”
Section: Discussionsupporting
confidence: 84%
“…In line with this argument, Laillier et al (64) found that cognitive measures partially mediated the age effect on cognitive and affective ToM performances in healthy subjects using the MASC. In addition, dissociations between cognitive and behavioral assessments have been found in TBI with patients performing within the normal range on the cognitive battery while demonstrating significant behavioral changes (21). Such findings indicate that cognitive and behavioral dysexecutive syndromes may be dissociated (19) and support the hypothesis that behavioral disorders cannot always be explained by cognitive disorders.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations